BORDER CHECK TRAINING IN FINLAND - COMPARISON OF E-LEARNING TOOLS FOR PRACTICAL AND LEGAL STUDIES - Lindblom-Häkkinen, Sari; Heinikoski, Saila; Anttila, Maisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper discusses the possibilities and challenges in applying e-learning tools in border check training, comparing the training of legal issues and border check practices. The main research question of the paper is how e-learning is utilised in and comport with border guard training. In pedagogical discussion, one of the most popular strands in the e-learning context is the method called "flipped classroom". In a flipped classroom, part of so-called blended learning, students study e-learning material before they start practicing their skills in simulated situations. We examine in which situations related to border checks flipped learning could be appropriate and beneficial and what sort of skills can best be learned through them. Practical skills are of course crucial, and after classroom learning in border guard training, working practice periods are obligatory for students. With the above-mentioned pedagogical concepts in mind, we first utilise content analysis based on the Community of Inquiry (CoI) framework, analysing how the online platform supports practical skills. Secondly, we bring the training period into conversation highlighting its importance as a learning method. The empirical material of the paper consists of educational documents, e-learning material used in border check and legal training as well as interviews and observation with trainers and teachers at the Finnish Border and Coast Guard Academy. The paper illustrates that e-learning tools are particularly useful in rehearsing to apply theoretical knowledge in practical situations. Still, the training period cannot be replaced with any methods. However, basing on the tentative analysis of empirical data before training period, flipped learning method seems to be very effective learning method.